The effect of the cyclic GMP-AMP synthase-stimulator of interferon genes signaling pathway on organ inflammatory injury and fibrosis - Liu, Yuliang; Li, Yihui; Xue, Li; Xiao, Jie; Li, Pengyong; Xue, Wanlin; Li, Chen; Guo, Haipeng; Chen, Yuguo (Frontiers in Pharmacology, 2022)
The cGAS-STING signal transduction pathway is critical in innate immunity, infection, and inflammation. In response to pathogenic microbial infections and other conditions, cyclic GMP-AMP synthase (cGAS) recognizes abnormal DNA and initiates a downstream type I interferon response. This paper reviews the pathogenic mechanisms of stimulator of interferon genes (STING) in different organs, including changes in fibrosis-related biomarkers, intending to systematically investigate the effect of the cGAS-STING signal transduction in inflammation and fibrosis processes. The effects of STING in related auto-inflammatory and neurodegenerative diseases are described in this article, in addition to the application of STING-related drugs in treating fibrosis.